Pariwisata Dalam Tinjauan Pendidikan: Studi Menuju Era Revolusi Industri - Erwin Akib (Politeknik Pariwisata Makassar, Indonesia, 2020)
This paper is to describe and answer the challenges faced by ¬edu-Tourism in the era of the industrial revolution 4.0. The method used is a qualitative approach using a library research approach, which is focused on making the decision process and analyzing the relationship of dynamic phenomena with scientific logic. The results of this discussion are 1) in the development of tourism, there are several aspects needed to support the development such as physical aspects, aspects of tourism attractiveness, accessibility aspects, aspects of activities and facilities, as well as socio-economic and cultural aspects, 2) the concept of deliberate educational tourism designed specifically to meet the scientific capacity of students to fill national insights with travel activities to recognize the region and the potential of local resources between regions, districts, provinces and inter-islands throughout the country, 3) industry 4.0 implementation can be one of the strategies to create an economy based digital especially in the development of tourism education in accordance with the direction of the road map Making Indonesia 4.0 in an effort to improve the performance of the national industry in the field of tourism, 4) there are five skills that become top in the development of the industrial revolution 4.0. The skills are Cognitive Abilities, System Skills, Complex Problem Solving, Content Skills, and Process Skills. To respond to the future development of the industrial revolution 4.0, a strong commitment is needed.